Parent experiences of diabetes care questionnaire (PEQ-DC): reliability and validity following a national survey in Norway - Hilde Hestad Iversen; Ylva Helland; Oyvind Bjertnaes; Torild Skrivarhaug (BMC, 2018)
Abstract Background Patient experiences are acknowledged as an important aspect of health care quality but no validated instruments have been identified for the measurement of either parent or patient experiences with outpatient paediatric diabetes care. The aim of the current study was to assess the psychometric properties of a new instrument developed to measure parent experiences of paediatric diabetes care at hospital outpatient departments in Norway. Methods The development of the questionnaire was based on a literature review of existing questionnaires, qualitative interviews with both parents and children/adolescents, expert-group consultations, pretesting of the questionnaire and a pilot study. The national pilot study included parents of 2606 children/adolescents aged 0-17 years with Type 1 Diabetes registered in The Norwegian Childhood Diabetes Registry, a nationwide, population-based registry. Levels of missing data, ceiling effects, factor structure, internal consistency, item discriminant validity and construct validity were assessed. Results A total of 2606 patients were included in the survey, but 80 were excluded due to incorrect addresses. 1399 (55%) parents responded to the questionnaire. Low levels of missing or "not applicable" responses were found for 31 of the 35 items (< 10%), and 27 of 35 items were below the ceiling-effect criterion. Psychometric testing and theoretical considerations identified six scales: Consultation (six items), organisation (five items), equipment (three items), nurse contact (four items), doctor contact (four items) and outcome (five items). All six scales met the 0.7 criterion for Cronbach's alpha (range: 0.71-0.90). As expected, each item had a higher correlation with its hypothesised scale than with any of the other five scales. The construct validity of the Parent Experiences of Diabetes Care Questionnaire (PEQ-DC) was supported by 17 out of 18 associations with variables expected to be related to parent experiences. Conclusion The psychometric testing of the PEQ-DC showed good evidence for data quality, internal consistency and construct validity. The instrument includes important aspects of diabetes care at paediatric outpatient departments from the perspective of the parent. The content validity of the PEQ-DC was secured by a rigorous development process, and the instrument was tested following a national survey in Norway, securing generalisability across Norway.